Transiciones sustentables en ciudades: diálogo de saberes y agroecología urbana en San Carlos de Bariloche, Río Negro, Argentina - Mattioli, Denise (2025)
The effects of contemporary territorial transformations are driving to rethink cities from innovative perspectives. The management of socio-food systems is a huge challenge is in the face of the advancing urban and productive frontier. Agroecology offers viable tools for their redesign, combining ecological, economic, and social principles. With the aim of exploring the relationship between urbanization, the environment, and experiences of social innovation, this paper reflects on a process of dialogue between universities, the state, and the community of San Carlos de Bariloche (Río Negro, Argentina) aimed at promoting agroecology in urban gardens. The multi-stakeholder coordination in research, outreach, and technology transfer combined participatory action research strategies with the use of qualitative and quantitative tools. It is argued that strengthening local capacities is essential to promoting sustainable transitions in urban ecosystems. The relevance of co-production and co-design approaches for urban planning and urban-environmental studies is highlighted.